Antimicrobial stewardship implementation before and during the COVID-19 pandemic in the acute care settings: a systematic review - Rasha Abdelsalam Elshenawy; Nkiruka Umaru; Amal Bandar Alharbi; Zoe Aslanpour (BMC, 2023)
Abstract Introduction Antibiotics are widely administered for various indications, leading to increased antimicrobial resistance (AMR) in acute care hospitals. Since the onset of the COVID-19 pandemic, Antimicrobial Stewardship (AMS) effective strategies should be used to maintain the rational use of antibiotics and decrease the threat of Antimicrobial Resistance (AMR). Aim This systematic literature review aims to investigate the AMS intervention Before-the-pandemic (BP) and During-the-pandemic (DP) from the literature. Design and setting Systematic literature review of primary studies on AMS implementation in acute care settings. Methods Relevant studies published between 2000 and March 2021 were obtained from Medline (via PubMed), OVID, CINAHL, International Pharmaceutical Abstracts, Psych Info, Scopus, Web of Science, Cochrane Library, OpenGrey, and Google Scholar, using a comprehensive list of search terms. Public Health England (PHE) toolkit was agreed upon as a gold standard for the AMS implementation. Results There were 8763 articles retrieved from the databases. Out of these, 13 full-text articles met the inclusion criteria for the review. The AMS implementation was identified in the included studies into AMS strategies (Core strategies & Supplemental strategies), and AMS measures BP and DP. Conclusion This Systematic literature review summarises AMS implementation strategies and measures all over the previous 20 years of research. There are many lessons learnt from COVID-19 pandemic. The proper selection of the AMS implementation strategies and measures appeared to be effective in maintaining the appropriate use of antibiotics and decreasing the AMR threat, especially during the COVID-19 pandemic. Further studies are required to provide empirical data to evaluate the AMS implementation and identify which of these strategies and measures were effective BP and DP. In order to be prepared for any emergency/crisis or future pandemics.